CICLO ECONÓMICO Y MORA LEGAL EN EL SISTEMA FINANCIERO COSTARRICENSE - Chacón, Marlon Yong (2022)
This article analizes the behaviour of non-performing loans in the financial system of Costa Rica from 1999 to 2010, in particular in state and private banks during the recent international crisis. Economic models are used to test for causality relationships between non-performing loans, the economic cycle and the financial cycle. It is concluded that the quality of credit assets in the financial sector of Costa Rica is affected by both the economic and the financial cycles. Furthermore, even though the effects of the recent financial crisis was similar on state and private banks, the latter adopt measures that reduce  accounting non-performing loans faster than their state owned counterpart.